Finite Element Method for a Nonlinear Differential Equation Describing Crystal Surface Growth - Zhao, Xiaopeng; Liu, Fengnan; Liu, Bo (Mathematical Modelling and Analysis, 2014)
In this paper, for a nonlinear differential equation describing crystal surface growth, the finite element method is presented. A nice order error estimates is derived by means of a finite element projection approximation.